2021
DOI: 10.3389/fgene.2021.598635
|View full text |Cite
|
Sign up to set email alerts
|

Association of CCR5Δ32 Deletion and Human Cytomegalovirus Infection With Colorectal Cancer in Tunisia

Abstract: Background and objectives: Human cytomegalovirus (HCMV) and genetic polymorphisms of the chemokine receptor 5 have been suggested as factors associated with the progression of colorectal cancer (CRC). The aim of the study was to evaluate the associations of both CCR5Δ32 genetic deletion and/or HCMV virus infection with CRC in Tunisia. Materials and methods: The association between HCMV and CRC was validated by Nested PCR technology performed for HCMV and HCMV-specific serum IgG and IgM antibodies were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The PI3K-Akt signaling pathway promotes liver cancer cell proliferation and metastasis [60]. In human cytomegalovirus infection, there is association of CCR5Δ32 deletion and human cytomegalovirus infection with colorectal cancer in Tunisia [61]. Kaposi sarcoma-associated herpesvirus infection regulates proliferation of glioma stem-like cells [62], relieves the Warburg effect through p53 activation, thereby inhibiting breast cancer cell growth [63], inhibits renal cancer cell growth by regulating the p53 signaling pathway [48], suppresses lung cancer growth by activating the p53 signaling pathway [64], promotes cholangiocarcinoma cell proliferation, migration, and invasion by decreasing p53 expression [65], and promotes pancreatic cancer growth and metastasis through the p53 transcriptional pathway [66].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway promotes liver cancer cell proliferation and metastasis [60]. In human cytomegalovirus infection, there is association of CCR5Δ32 deletion and human cytomegalovirus infection with colorectal cancer in Tunisia [61]. Kaposi sarcoma-associated herpesvirus infection regulates proliferation of glioma stem-like cells [62], relieves the Warburg effect through p53 activation, thereby inhibiting breast cancer cell growth [63], inhibits renal cancer cell growth by regulating the p53 signaling pathway [48], suppresses lung cancer growth by activating the p53 signaling pathway [64], promotes cholangiocarcinoma cell proliferation, migration, and invasion by decreasing p53 expression [65], and promotes pancreatic cancer growth and metastasis through the p53 transcriptional pathway [66].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recently Chelbi et al . showed no difference of UL55 gene detection in tumor versus peritumor tissues [ 25 ]. Also, earlier studies found no relation between HCMV and CRC [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%